KEBIJAKAN BUMG DALAM MENDUKUNG GAMPONG MANDIRI MELALUI KAPASITAS GAMPONG WISATA MANEE KAREUNG KOTA LHOKSEUMAWE - Nurmasyahyati Nurmasyahyati; Fidhia Aruni; Ratna Farida; Nurzamli Nurzamli (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
BUMG is one of the forces that can encourage the creation of economic improvement for villagers or gampongs based on the variety of potentials they have and BUMG management must be able to manage and develop businesses by looking at existing opportunities and understanding the demands of the community. The BUMG policy in Manee Kareung supports Gampong’s economic independence through the development of Tourism Villages. The research method used is descriptive qualitative. Implementing BUMG policies in the development of Tourism Villages is the focus of research. Sources of data obtained through literacy studies are available online and offline, such as scientific journals, books, and news from trusted sources. The results show that at the organizational level, BUMG Manee Kareung has not shown functional capacity in aspects of external partnerships, aspects of tourism development potential, and aspects of tourism village promotion. Likewise in the aspects of leadership and coordination, it shows a lack of capacity and individuals also do not have the functional capacity to spearhead the development of tourism potential. Therefore, this study provides several recommendations for further research, especially regarding institutional capacity at the system level. At the system level, research on the relationship between individuals, informal groups, and formal organizations that generate social capital and policies carried out by the Tourism Office and the Gampong Government related to the development of tourism villages.